Prinsip Kehati-Hatian (Prudential Banking Principles) Dalam Pembiayaan Syariah Untuk Mengurangi Resiko Kredit Macet (Non-Performing Loan) - Ade Salamah (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2023)
The community's need for financial institutions, especially bank financial institutions, both for personal and business purposes, is increasing from year to year. Banks as one of the financial institutions are competing to maximize their lending to the public and to companies with the promised conveniences. This is in accordance with one of the main functions of banking, namely as an institution that collects funds from the public in the form of savings and distributes them back to the community in the form of credit or financing. The purpose of applying the precautionary principle is so that banks are always in good health, in a state of liquid and solvent. In addition, the precautionary principle also anticipates the occurrence of bad loans and for the sake of maintaining public trust in banking institutions. If this principle is ignored by banking institutions, it will have a negative impact, namely in the form of losses and risks for the bank itself..